Burning mouth syndrome: Current concepts - Cibele Nasri-Heir; Julyana Gomes Zagury; Davis Thomas; Sowmya Ananthan (Wolters Kluwer Medknow Publications, 2015)
Burning mouth syndrome (BMS) is a chronic pain condition. It has been described by the International Headache Society as "an intra-oral burning or dysesthetic sensation, recurring daily for more than 2 h/day for more than 3 months, without clinically evident causative lesions." BMS is frequently seen in women in the peri-menopausal and menopausal age group in an average female/male ratio of 7:1. The site most commonly affected is the anterior two-thirds of the tongue. The patient may also report taste alterations and oral dryness along with the burning. The etiopathogenesis is complex and is not well-comprehended. The more accepted theories point toward a neuropathic etiology, but the gustatory system has also been implicated in this condition. BMS is frequently mismanaged, partly because it is not well-known among healthcare providers. Diagnosis of BMS is made after other local and systemic causes of burning have been ruled out as then; the oral burning is the disease itself. The management of BMS still remains a challenge. Benzodiazepines have been used in clinical practice as the first-line medication in the pharmacological management of BMS. Nonpharmacological management includes cognitive behavioral therapy and complementary and alternative medicine (CAM). The aim of this review is to familiarize healthcare providers with the diagnosis, pathogenesis, and general characteristics of primary BMS while updating them with the current treatment options to better manage this group of patients.